Influência do estresse na qualidade do sono de idosos da comunidade - Guiesi, Pedro Henrique Machado (Universidade Federal de São Carlos, 2021)
Sleep is a vital function that has a restorative and regulatory action on organic systems. Several studies indicate that sleep is negatively modified with aging. Stress leads to a state of alarm, resistance and exhaustion with physical and emotional changes. Considered a variable that, like aging, can bring about changes in sleep patterns. The present study aimed to identify the association between stress and sleep quality in community-dwelling elderly. This is a research with a quantitative, descriptive and transversal design. The sample was found by elderly people registered in Family Health Units in the city of São Carlos, São Paulo. Data collection was performed according to the application of a sociodemographic and health characterization questionnaire (this will include the use of sleeping medications, physical activity, weekly physical activity time, period of activities and comorbidities), Scale of Geriatric Depression (GDS-15), Perceived Stress Scale and Pittsburgh Sleep Quality Index (PSQI). Descriptive and comparative statistical analyzes were performed. The sociodemographic profile of the sample was young (M=69.88; Md=70.00; SD=6.92). Education was low (M=3.03; Md=3.00; SD=2.92). Individual and family income were less than 1.5 and 2.5 minimum wages, respectively (individual income: M=1201.87; Md=998.00; SD=886.50; family income: M=2328.39; Md=2000.00; SD=1121.93). The elderly were predominantly female (54.4%, n=67), married (92.7%, n=114), mulatto or brown (68.3%, n=166), Catholic (53.7%, n=66), retired (79.7%, n=98) and with a perception of insufficient income to meet the demands of daily life (57.7%, n=71). Regarding the variable presence of comorbidities according to sleep quality, the analyzes showed differences in the quality of sleep of elderly people with arterial hypertension (p=0.019), arthritis (p=0.026), anxiety (p=0.000) and depression (p =0.006). The total score related to poor sleep quality was significantly higher among the elderly with high stress (Low stress group: M=6.05; Md=6.00; SD=3.28; High stress group: M= 9.06; Md=9.00; SD=4.29) (U=1117.50, p=0.000). Analysis of covariance revealed that there is an effect of depressive symptoms on overall sleep quality scores [F (1, 120)=6.381, p=0.013]. However, even considering depressive symptoms as a covariate, the difference in sleep quality according to the level of stress remained significant [F (1, 120)=5.820, p=0.017]. It is concluded that high levels of stress lead to worse sleep quality.
Influence of stress on sleep quality of community elders
Keywords: Estresse; Sono; Idoso; Stress; Sleep; Aged; CIENCIAS DA SAUDE